Direct solid-state growth of Fe/N Co-doped coordination structure between carbon nanotubes and ultra-thin porous carbon nanosheets towards oxygen reduction reaction. (1st September 2020) - Ma, Yinghua; Song, Ailing; Yan, Shanshan; He, Haoyan; Shao, Guangjie
Abstract: Developing sufficient resources, low prices and easy availability non-noble metal-based catalysts for the oxygen reduction reaction (ORR) to substitute Pt-based materials is extremely desirable but still a grand challenge.Notably, a facile and cost-efficient pyrolysis strategy is demonstrated to fabricate a three-dimensional (3D) structural ORR electrocatalyst (denoted as Fe@N–CNS/CNTS)based on Fe/N Co-doped carbon nanotubes (NCNT) with ultra-thin porous carbon nanosheets (NCNS) via a ZnCl2 -assisted approach. The ZnCl2 play a crucial role in creating the 3D porous structure which is more beneficial for enhancing specific surface area and exposing sufficient active sites. Anecdotally, the rationally designed catalysts have multifactorial synergistic function of ultra-thin porous NCNS, NCNTS with iron carbide and oxide (Fe3 C, Fe2 O3 ). The prepared optimal Fe@N-CNS/CNTS-0.5 revealed catalytic performance with onset potential of 0.983V (vs RHE) and relatively small Tafel slope of 63 mV dec −1 in 0.1 M KOH solution. More importantly, after 25, 000s chronoamperometry, the as-prepared electrocatalyst possessed excellent durability with only 7% current decay surpassing that of the 20% Pt/C (17%), which is also further evaluated in realistic quasi-solidstate flexible Zn-air batteries. As a consequence, this strategy provided a universal approach for future development of the multifunctional cathode catalysts. Graphical abstract: Image 1 Highlights: A three-dimensional network structure with coordination structure between carbon nanotubes and carbon layers using a simple novel method. The rationally designed catalysts have multifactorial synergistic function of ultra-thin porous carbon nanosheets, carbon nanotubes with metal particles. The structure possessed more macro-/meso-/micropores under the gasification of ZnCl2, which promoted the adsorption and desorption of O2 .